2015
DOI: 10.1111/obr.12244
|View full text |Cite
|
Sign up to set email alerts
|

Complex association between body weight and fracture risk in postmenopausal women

Abstract: Osteoporosis is a common disease, characterized by low bone mass with micro-architectural disruption and skeletal fragility, resulting in an increased risk of fracture. A substantial number of studies has examined the possible relationship between body weight, bone mineral density and fracture risk in post-menopausal women, with the majority of them concluding that low body weight correlates with increased risk of fracture, especially hip fracture. Controversies about the potential protective effect of obesity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 82 publications
2
44
0
3
Order By: Relevance
“…It can therefore be hypothesised that the absence of significant deterioration in bone metabolism may be the result of a protective effect against bone mass loss and that this effect is due to the very state of being overweight or to the slowing down of the metabolism [18]. Moreover, our data show that BMD is not influenced by other factors of bone compromission, except for weight and menopausal status.…”
Section: Considerations On Frmentioning
confidence: 52%
“…It can therefore be hypothesised that the absence of significant deterioration in bone metabolism may be the result of a protective effect against bone mass loss and that this effect is due to the very state of being overweight or to the slowing down of the metabolism [18]. Moreover, our data show that BMD is not influenced by other factors of bone compromission, except for weight and menopausal status.…”
Section: Considerations On Frmentioning
confidence: 52%
“…Obesity per se is increasingly recognized as a state of heightened fracture risk in both men and women [7,8]. For instance, a study involving over 60,000 women from 10 countries revealed an association between BMI ≥ 30 kg/m 2 and increased risk of ankle and upper leg fractures (with reduced risk of wrist fractures) [7], and a similar correlation was also found in men, albeit only after correction for the increased BMD generally associated with obesity [8], and not without controversy [13]. Interestingly, these fracture sites [7] differ from the fracture sites most commonly seen in osteoporosis, which are the wrist, upper arm, rib, hip and spine [7].…”
Section: Introductionmentioning
confidence: 99%
“…30 kg/m 2 and increased risk of ankle and upper leg fractures (with reduced risk of wrist fractures), (10) and a similar correlation was also found in men, albeit only after correction for the increased BMD generally associated with obesity, (11) and not without controversy. (12) Whether or not obesity per se has an effect on fracture risk, emerging evidence suggests that obesity treatment, namely bariatric surgery-which induces weight losses of up to 75% of excess body weight that are maintained for up to 10 to 14 years postsurgery (13) -results in bone loss. (14,15) However dietinduced weight loss, not bariatric surgery, with or without concomitant physical activity, is seen as the first treatment option for overweight and obesity.…”
Section: Introductionmentioning
confidence: 99%